Texture analysis in ultrasound images of carotid plaque components of asymptomatic and symptomatic subjects - Loizou, Christos P.; Pantziaris, Marios; Theofilou, Marilena; Kasparis, Takis; Kyriakou, Efthivoulos (My University, 2013)
There are indications that the texture of certain components of atherosclerotic carotid plaques in the common carotid artery (CCA), obtained by high resolution ultrasound imaging, may have additional prognostic implication for the risk of stroke. The objective of this study was to perform texture analysis of the middle component of atherosclerotic carotid plaques in 230 CCA plaque ultrasound images (115 asymptomatic and 115 symptomatic). These were manually delineated by a neurovascular expert after normalization and despeckle filtering using the linear despeckle filter (DsFlsmv). Texture features were extracted from the middle plaque component. We found statistical significant differences for some of the texture features extracted, between asymptomatic and symptomatic subjects. The results showed that it may be possible to identify a group of patients at risk of stroke (asymptomatic versus symptomatic) based on texture features extracted from the middle component of the atherosclerotic carotid plaque in ultrasound images of the CCA. © IFIP International Federation for Information Processing 2013.
Keywords: Atherosclerotic carotid plaque components; Texture analysis; Ultrasound image; Carotid artery